Persistent IgG anticardiolipin autoantibodies are associated with post-COVID syndrome. (December 2021) - Bertin, Daniel; Kaphan, Elsa; Weber, Samuel; Babacci, Benjamin; Arcani, Robin; Faucher, Benoit; Ménard, Amélie; Brodovitch, Alexandre; Mege, Jean Louis; Bardin, Nathalie
Highlights: To date, no biological markers have been proposed to predict post-coronavirus disease 2019 (COVID-19) syndrome (PCS). Immunoglobulin G (IgG) anticardiolipin autoantibodies (aCL) are associated with the severity of COVID-19. This article reports a case of persistent IgG aCL positivity in a patient with PCS. Persistence of aCL positivity could be a biological predictor of PCS. Abstract: Persistence of various symptoms in patients who have recovered from coronavirus disease 2019 (COVID-19) was recently defined as 'long COVID' or 'post-COVID syndrome' (PCS). This article reports a case of a 58-year-old woman who, although recovering from COVID-19, had novel and persistent symptoms including neurological complications that could not be explained by any cause other than PCS. In addition to a low inflammatory response, persistence of immunoglobulin G anticardiolipin autoantibody positivity and eosinopenia were found 1 year after acute COVID-19 infection, both of which have been defined previously as independent factors associated with the severity of COVID-19. The pathophysiological mechanism of PCS is unknown, but the possibility of persistence of the virus, especially in the nervous system, could be suggested with a post-infectious inflammatory or autoimmune reaction.